STRATEGI KOALISI PARTAI TERHADAP PEMENANGAN PASANGAN HARIS-ZARDEWAN DALAM PEMILIHAN KEPALA DAERAH KABUPATEN PELALAWAN TAHUN 2015 - Dery Setyadi; Raja Muhammad Amin (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2017)
The purpose of this study is to illustrate and analyze party coalition's strategy on the victory of Haris-Zardewan pair in the election of Pelalawan Regency head of the year 2015. And to illustrate and analyze the factors that cause political parties wanting to be coalition for the victory of the Haris-Zardewan pair in the election Head of the district of Pelalawan Regency in 2015. The type of research used is qualitative research. In defining informants using snowball sampling technique. The informant in this study is taken by purposive sampling, where selecting competent informants in the field and can provide the information needed by the coalition party to support / win the Haris-Zardewan pair in Pelalawan Regency Data collection methods are interviews and documentation. The method of data analysis is qualitative, which is by describing the data in the form of detailed and complete sentences (intact) to answer all the problems studied.Keywords: strategy, party coalition